Nutrient profiling assessment of packaged snack foods with nutrition-related claims available on the Indian market - Bhatnagar, Amisha; Choudhary, Monika; Kumar, Vikas; Singh, Vicky; Kaur, Prabhdeep (Frontiers in Nutrition, 2024)
Background: Food packaging includes labels with specific nutrient contents to provide consumers with nutritional information. Legislative actions and consumers' growing interest in nutrition information have led to an increase in the disclosure of nutrition information. The study was planned to examine packaged snack foods carrying nutrient claim with respect to nutrition labelling.The selected packaged chips were divided into categories based on the primary ingredients mentioned on the nutrition label, such as cereal/pseudocereal based, millet based, vegetable based and pulses/legume based chips. Four threshold levels such as total sugar, sodium, total fat and saturated fat were used for categorization.Results: Out of total 23 packaged chips, the corresponding 2, 7, 8 and 13 products were having higher content of sugar, saturated fat, sodium and total fat than the threshold levels. A significant (p≤0.01) difference was observed in the values of nutrients analysed through laboratory methods in comparison to the values given on nutrition label in majority of the products.Majority of the products belonged to national brands and differed from the nutrition related information given in product label in terms of nutrient content claim.